Peningkatan Pengetahuan Masyarakat melalui Pelatihan Pengolahan Jahe Merah menjadi Chew Gummy di Desa Senggigi - Wahida Hajrin; Yohanes Juliantoni; Windah Anugerah Subaidah (Institut Pertanian Bogor, 2021)
Red ginger is a beneficial rhizome used to treat sore throats, dry cough, colic, rheumatism, headache, and flatulence. This community service aims to provide knowledge about the benefits of red ginger for health and how to process red ginger to a worth to sell products. The knowledge about the benefits of red ginger for health presented directly and the processing of chew gummy demonstrated in front of the participants. The community service was carried out at the Senggigi Village Office by involving by involving cadre of Posyandu and PKK asparticipants. The participants are given a pre-test and post-test to determine the increase in participant understanding. The results showed an increase in post-test scores from pre-test values about the benefits of red ginger and its processing. Participants understand the benefits of red ginger for health and can process red ginger into chew gummy preparations.